Peran Zakat Dalam Pemberdayaan Ekonomi Perempuan: (Studi Kasus Pemberdayaan Rumah Zakat Terhadap Kelompok Usaha Bersama (KUBE) Rajut Hijau Indonesia di Dusun Karangasem, Sidomulyo, Pengasih, Kulonprogo Yogyakarta) - Setiawan, Heri; Sujono, Rusny Istiqomah; Ismiati, Baiq; Kamal, Al Haq (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The problem of women who are vulnerable to socio-economic conditions is still a problem that occurs in one of the sub-districts in Kulonprogo, to be precise in Karangasem Hamlet, Sidomulyo Village, Pengasih District, Kulonprogo Regency, DIY Province. Evidenced by data from 2018 to date which shows that there are still 340 Socio-Economic Vulnerable Women in the Pengasih sub-district and occupy the third most position for Socio-Economic Vulnerable Women from 12 sub-districts in Kulonprogo. However, some women with a low economy are still trying to meet the needs of their families and try to rise from their poverty by continuing to try to carry out their expertise, namely knitting. The method used in this research is a qualitative research method, where researchers obtain data by means of interviews, field observations, and documentation, then the results of the data obtained will be analyzed using SWOT analysis. The results of this study show that there are many impacts that have occurred with the existence of the Yogyakarta Zakat House through the development of zakat funds which are distributed to KUBE Kulonprogo Knitting Bag business actors, especially for women by looking at the results of the SWOT Matrix